Hadith About Motivation in Economics: (Hands Up Are Better Than Hands Down) - Afif Musthafa; Ahmad Muhammad Tidjani (Values: Jurnal Kajian Islam Multidisiplin, 2024)
This study examines the meaning and relevance of the hadith "The upper hand is better than the lower hand" in the context of Islamic economic motivation. Utilizing a literature review method, the research analyzes the normative and applicative aspects of the hadith, particularly in relation to modern economic activities and scholarly interpretations. The findings highlight several key points: (1) the significance of productivity, economic independence, and work ethics in Islam; (2) its relevance to modern economic principles such as entrepreneurship, innovation, and corporate social responsibility; (3) scholarly interpretations that emphasize encouragement to work diligently, achieve financial independence, and actively assist others; and (4) the consistency of this hadith with other Islamic teachings that promote productivity and contributions to social welfare. Furthermore, the study underscores the importance of balancing personal effort and reliance on Allah in seeking sustenance. In conclusion, Islam encourages its followers to be proactive, productive, and generous, positioning economic endeavors as both acts of worship and contributions to social well-being.